Formyl peptide receptor-1 activation exerts a critical role for the dynamic plasticity of arteries via actin polymerization. (March 2019) - Wenceslau, Camilla F.; McCarthy, Cameron G.; Szasz, Theodora; Calmasini, Fabiano B.; Mamenko, Mykola; Webb, R. Clinton
Graphical abstract: Schematic proposing that formyl peptide receptor-1 (FPR-1) play a role in the vascular function. Formyl peptide receptor (FPR-1), an innate immune system receptor, mediates vascular plasticity during physiological conditions. Upon activation (by agonist or stretch), FPR-1 triggers actin polymerization via an integrated network with Cav 1.2 and RhoA. Future studies are needed to dissect the mechanisms associated with FPR-1 activation and its functions as a mechanosensor-like receptor and vascular-immuno network during perturbations. Abstract: Several human diseases, include cancer and stroke are characterized by changes in immune system activation and vascular contractility. However, the mechanistic foundation of a vascular immuno-physiology network is still largely unknown. Formyl peptide receptor-1 (FPR-1), which plays a vital role in the function of the innate immune system, is widely expressed in arteries, but its role in vascular plasticity is unclear. We questioned why a receptor that is crucial for immune defense, and cell motility in leukocytes, would be expressed in vascular smooth muscle cells (VSMCs). We hypothesized that activation of FPR-1 in arteries is important for the temporal reorganization of actin filaments, and consequently, changes in vascular function, similar to what is observed in neutrophils. To address our hypothesis, we used FPR-1 knockout and VSMCs lacking FPR-1. We observed that FPR-1 activation induces actin polymerization in wild type VSMCs. Absence of FPR-1 in the vasculature significantly decreased vascular contraction and induced loss of myogenic tone to elevated intraluminal pressures via disruption of actin polymerization. Actin polymerization activator ameliorated these responses. In conclusion, we have established a novel role for FPR-1 in VSMC contractility and motility, similar to the one observed in sentinel cells of the innate immune system. This discovery is fundamental for vascular immuno-pathophysiology, given that FPR-1 in VSMCs not only functions as an immune system receptor, but it also has an important role for the dynamic plasticity of arteries.